Kesediaan UKM Untuk Mendapatkan Sertifikat Halal di Kota Pekanbaru - Rahmayanti, Sri; Rosyetti, Rosyetti; Misral, Misral; Perdana, Riky (Akuntansi & Ekonomika, 2024)
Law Number 33 of 2014 and Government Regulation Number 39 of 2021, products, basic ingredients, food and beverage additives; and as well as services and slaughtered animals are halal certified until 17 October 2024, after which sanctions apply. Respondents 50 respondents, the results that awareness about halal, knowledge about halal, and the difficulty of obtaining certification do not affect the willingness of halal certification. The difficulty in taking care of certification is not a barrier in applying for certification. However, internal and external encouragement, such as the desire for product standardisation, government regulations and consumer response to halal products that encourage willingness to halal certification. The results of encouragement and real help motivate business actors to take care of halal certification for their products.